1994
DOI: 10.1128/iai.62.11.5075-5084.1994
|View full text |Cite
|
Sign up to set email alerts
|

A family of phase- and size-variant membrane surface lipoprotein antigens (Vsps) of Mycoplasma bovis

Abstract: A set of strain-and size-variant highly immunogenic membrane surface protein antigens of Mycoplasma bovis, which has been identified by a monoclonal antibody, is shown in this report to make up a family of antigenically and structurally related lipid-modified proteins, designated Vsps (variable surface proteins). By systematic analysis of several isogenic clonal lineages of the type strain PG45, three members of this family have been identified, VspA, VspB, and VspC, each of which was shown to undergo independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(74 citation statements)
references
References 27 publications
3
70
0
1
Order By: Relevance
“…No growth inhibition oc-curred and significant modifications appeared only for inocula of I-100 cells. The presence of such 'escape variants' within an initial mycoplasma population of only 1llOO cells is statistically unlikely since the frequency of Vsps was reported to range between I OF" and 1O-5 per cell per generation [16]. We therefore concluded that the observed changes in Vsp surface antigen expression were indeed induced by the respective antibody as sensory signal.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…No growth inhibition oc-curred and significant modifications appeared only for inocula of I-100 cells. The presence of such 'escape variants' within an initial mycoplasma population of only 1llOO cells is statistically unlikely since the frequency of Vsps was reported to range between I OF" and 1O-5 per cell per generation [16]. We therefore concluded that the observed changes in Vsp surface antigen expression were indeed induced by the respective antibody as sensory signal.…”
Section: Discussionmentioning
confidence: 80%
“…M bovis strain 1067 was isolated in 1983 from a case of bovine mastitis [24] and successfully used to experimentally induce reproducible arthritis in calves [20]. Clonal variants of M. bovis type strain PG45 expressing a single size variant of VspA (65 and 63 kDa), VspB (46,44.5,43 or 42 kDa) or Vsp C (79 or 75 kDa), or lacking all three Vsps (designated ABC-OK) have been previously described [16]. Each organism was propagated at 37°C in a standard mycoplasma medium [23].…”
Section: Mycoplasmas and Culture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, pMG41 and pMI41 are the first reported examples of variable surface proteins in mycoplasmas which are not described as integral membrane proteins. All other described phase-variable mycoplasma antigens so far are integral membrane proteins that are membrane-anchored either via lipid [12, 14,17] or via hydrophobic transmembrane domains (191; D. Yogev, D. Menaker and R. Rosengarten, submitted).…”
Section: Discussionmentioning
confidence: 99%
“…for Triton X-l 14 (TX-l 14; Boehringer Mannheim) phase fractionation, SDS-PAGE and Western immunoblotting of mycoplasma proteins are described elsewhere [9,13,14]. For SDS-PAGE, samples (if not specifically indicated, each corresponding to 400 ~1 of a mid-log-phase culture) were boiled for 5 min under reducing conditions and loaded onto 9% polyacrylamide gels containing 3% (w/v) urea.…”
Section: Mycoplasma Antigen Analysismentioning
confidence: 99%